2008
DOI: 10.1074/jbc.m708580200
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Mitochondrial Methionine Sulfoxide Reductase B2 Protects Leukemia Cells from Oxidative Stress-induced Cell Death and Protein Damage

Abstract: According to the mitochondrial theory of aging, mitochondrial dysfunction increases intracellular reactive oxidative species production, leading to the oxidation of macromolecules and ultimately to cell death. In this study, we investigated the role of the mitochondrial methionine sulfoxide reductase B2 in the protection against oxidative stress. We report, for the first time, that overexpression of methionine sulfoxide reductase B2 in mitochondria of acute T-lymphoblastic leukemia MOLT-4 cell line, in which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 41 publications
5
57
0
Order By: Relevance
“…Deletion or knockdown of MsrA and MsrB genes in organisms ranging from bacteria to mammals results in increased sensitivity to oxidative stress (17,(19)(20)(21)(22)(23). Conversely, overexpression of these genes protects against oxidative stress-induced cell death (24)(25)(26)(27). In addition, fRMsr also has an antioxidant function in yeast (15).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion or knockdown of MsrA and MsrB genes in organisms ranging from bacteria to mammals results in increased sensitivity to oxidative stress (17,(19)(20)(21)(22)(23). Conversely, overexpression of these genes protects against oxidative stress-induced cell death (24)(25)(26)(27). In addition, fRMsr also has an antioxidant function in yeast (15).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations demonstrated that modulation of MsrA activity altered the level of reactive oxygen species; overexpression lowered the level in PC-12 cells (13), whereas lens cells lacking MsrA had an increased level (14). Increased expression of either MsrA in WI-38 fibroblasts or MsrB in MOLT-4 leukemia cells reduced the steady state level of oxidized proteins after a hydrogen peroxide challenge (15,16).Accumulation of oxidatively damaged proteins has been hypothesized to be an important mechanism of the aging process (17), and it is notable that overexpression of MsrA in Drosophila doubled the life span of the flies (10). We wished to determine whether the life extension observed in flies would also occur in mammals overexpressing MsrA and, if it did, whether the subcellular localization of MsrA were important.…”
mentioning
confidence: 99%
“…Several investigations demonstrated that modulation of MsrA activity altered the level of reactive oxygen species; overexpression lowered the level in PC-12 cells (13), whereas lens cells lacking MsrA had an increased level (14). Increased expression of either MsrA in WI-38 fibroblasts or MsrB in MOLT-4 leukemia cells reduced the steady state level of oxidized proteins after a hydrogen peroxide challenge (15,16).…”
mentioning
confidence: 99%
“…It has to be mentioned that the described modifications are mainly due to the action of ROS and that a large number of further amino acid derivates might also be formed by the action of reactive species derived from nitrogen monoxide or hypochloric acid (for details see Voss and Grune, 2006). proteins that accumulate upon oxidative stress by maintaining a low level of intracellular ROS (Cabreiro et al, 2008).…”
Section: Protein Oxidation Products From a Chemical Point Of Viewmentioning
confidence: 99%